Friday

March 27, 2015

March 27, 2015

Posted by **Austin** on Friday, January 4, 2013 at 12:04am.

e^x+e^-x=6

- math -
**Reiny**, Friday, January 4, 2013 at 12:34ame^x + e^-x = 6

e^x + 1/e^x = 6

hint:

let e^x = y

y + 1/y = 6

each term by y

y^2 + 1 = 6y

y^2 - 6y + 1 = 0

solve for y, then sub back into e^x

**Answer this Question**

**Related Questions**

Math - Simplify the following exponential expression. 120a^4b^2/-24a^9b^-15

Math - Use the expression 12*12 to answer the question below A. Write the ...

Math - Solve the following exponential equation 5^2-x=7^5x+7

Math!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!! - Solve the following exponential ...

math - change the exponential expression to an equivalent expression involving a...

college algebra, Please help!! - change the exponential expression to an ...

math - solve the following exponential equation e^x-4=-e^-x when I work i get x-...

math - translate the phrase into a mathematical expression and then evaluate it...

math - solve the following exponential equation e^x-4=-e^-x please show work

Math - Exponential equation - Solve the exponential equation. Express your ...